Metacognitive-Based Mathematics Learning for 21st-Century Students' Higher Order Thinking Skills - Masud B; Marwati Abd. Malik (International Journal of Artificial Intelligence Research, 2022)
. In order to face the challenges of 21st century life, mathematics learning must be directed to the development of students' Higher Order Thinking Skills (HOTS) because only these skills can lead students to be able to compete globally. HOTS ability can also improve critical and creative thinking skills. Therefore, learning must be directed at innovative and creative learning. One of the innovative learning offered in this study is metacognitive-based mathematics learning. This study aimed to improve students' Higher Order Thinking Skills. This experimental research was conducted by taking a sample in one of the Senior High Schools in Parepare City, namely class XI of Social Sciences at Senior High School 1 Parepare. This study was designed using a pre-test and post-test design with a metacognitive-based mathematics learning treatment. The results of the study were analyzed by normalized gain T-test. The results showed that there was an increase in students' Higher Order Thinking Skills through metacognitive-based mathematics learning at a significance level of α = 5%. In addition, it was found that the HOTS ability related to the students' Analyzing (C4) ability was in the very good category, while Evaluating (C5) ability and Creating (C6) ability were included in the good category, respectively. Therefore, the researchers hope that metacognitive knowledge become one of the alternatives that need to be developed to improve students' thinking skills.